Hybrid artificial intelligent systems : 8th International Conference, HAIS 2013, Salamanca, Spain, September 11-13, 2013. Proceedings - Pan, Jeng-Shyang; Polycarpou, Marios M.; Woźniak, Michał; Carvalho, Andre C. P. L. F.; Quintian, Héctor; Corchado, Emilio; Pan, Jeng-Shyang (Lecture Notes in Computer Science, 2013)
This volume constitutes the proceedings of the 8th International Conference on Hybrid Artificial Intelligent Systems, HAIS 2013, held in Salamanca, Spain, in September 2013. The 68 papers published in this volume were carefully reviewed and selected from 218 submissions. They are organized in topical sessions on Agents and Multi Agents Systems; HAIS Applications; Classification and Cluster Analysis; Data Mining and Knowledge Discovery; Video and Image Analysis; Bio-inspired Models and Evolutionary Computation; Learning Algorithms; Systems, MAN, and Cybernetics; Hybrid Intelligent Systems for Data Mining and Applications; Metaheuristics for Combinatorial Optimization and Modelling Complex Systems.